OPEN AND CONTROLLED COMPARATIVE STUDY ON 84 CASES-CYCLE OF ESSENTIAL DYSMENORRHOEA - Lozano Paredes, José (2015)
A group of 14 school-age patients with previous diagnosis of essential dysmenorrhea underwent an open, controlled comparative study over a period of six months, totaling 84 cases-cycle, in order to compare the action of mefenamic acid with that of a combination of four drugs incorporated into a pharmaceutical specialty. The final results showed a clear superiority of mefenamic acid (92% to 58%) relief of severe dysmenorrhea. In the group of patients with moderate dysmenorrhea, the results were similar. In both groups, the side effects were mild and transient.